Continuous Gossip-based Aggregation through Dynamic Information Aging - Graffi, Kalman; Rapp, Vitaly (Proceedings of the International Conference on Computer Communications and Networks (ICCCN'13))
Existing solutions for gossip-based aggregation in peer-to-peer networks use epochs to calculate a global estimation from an initial static set of local values. Once the estimation converges system-wide, a new epoch is started with fresh initial values. Long epochs result in precise estimations based on old measurements and short epochs result in imprecise aggregated estimations. In contrast to this approach, we present in this paper a continuous, epoch-less approach which considers fresh local values in every round of the gossip-based aggregation. By using an approach for dynamic information aging, inaccurate values and values from left peers fade from the aggregation memory. Evaluation shows that the presented approach for continuous information aggregation in peer-to-peer systems monitors the system performance precisely, adapts to changes and is lightweight to operate.

CONE-DHT: A distributed self-stabilizing algorithm for a heterogeneous storage system - Kniesburges, Sebastian; Koutsopoulos, Andreas; Scheideler, Christian (Proceedings of the 27th International Symposium on Distributed Computing (DISC))
We consider the problem of managing a dynamic heterogeneous storagesystem in a distributed way so that the amount of data assigned to a hostin that system is related to its capacity. Two central problems have to be solvedfor this: (1) organizing the hosts in an overlay network with low degree and diameterso that one can efficiently check the correct distribution of the data androute between any two hosts, and (2) distributing the data among the hosts so thatthe distribution respects the capacities of the hosts and can easily be adapted asthe set of hosts or their capacities change. We present distributed protocols forthese problems that are self-stabilizing and that do not need any global knowledgeabout the system such as the number of nodes or the overall capacity of thesystem. Prior to this work no solution was known satisfying these properties.

Comparison of Various Contract-Based Approaches for Specifying Behavior of On-The-Fly Computing Services - Jagannath, Kavitha

Comparative Evaluation of Peer-to-Peer Systems Using PeerfactSim.KOM - Feldotto, Matthias; Graffi, Kalman (Proceedings of the International Conference on High Performance Computing and Simulation (HPCS'13))
Comparative evaluations of peer-to-peer protocols through simulations are a viable approach to judge the performance and costs of the individual protocols in large-scale networks. In order to support this work, we enhanced the peer-to-peer systems simulator PeerfactSim.KOM with a fine-grained analyzer concept, with exhaustive automated measurements and gnuplot generators as well as a coordination control to evaluate a set of experiment setups in parallel. Thus, by configuring all experiments and protocols only once and starting the simulator, all desired measurements are performed, analyzed, evaluated and combined, resulting in a holistic environment for the comparative evaluation of peer-to-peer systems.

Cliquenbildung in verteilten Systemen - Blumentritt, Fritz

Ca-Re-Chord: A Churn Resistant Self-stabilizing Chord Overlay Network - Graffi, Kalman; Benter, Markus; Divband, Mohammad; Kniesburges, Sebastian; Koutsopoulos, Andreas (Proceedings of the Conference on Networked Systems (NetSys))
Self-stabilization is the property of a system to transfer itself regardless of the initial state into a legitimate state. Chord as a simple, decentralized and scalable distributed hash table is an ideal showcase to introduce self-stabilization for p2p overlays. In this paper, we present Re-Chord, a self-stabilizing version of Chord. We show, that the stabilization process is functional, but prone to strong churn. For that, we present Ca-Re-Chord, a churn resistant version of Re-Chord, that allows the creation of a useful DHT in any kind of graph regardless of the initial state. Simulation results attest the churn resistance and good performance of Ca-Re-Chord.

International as Opposed to Domestic New Venturing: The Moderating Role of Perceived Barriers to Internationalization. - Baum, M; Schwens, C; Kabst, Rüdiger (International Small Business Journal (ISBJ).)

Conjoint implications on job preferences: The moderating role of involvement. - Baum, M; Kabst, Rüdiger (International Journal of Human Resource Management (IJHRM).)

Business Process Models - Change Management - Gerth, Christian
In recent years, the role of process models in the development of enterprise software systems has increased continuously. Today, process models are used at different levels in the development process. For instance, in Service-Oriented Architectures (SOA), high-level business process models become input for the development of IT systems, and in running IT systems executable process models describe choreographies of Web Services. A key driver behind this development is the necessity for a closer alignment of business and IT requirements, to reduce the reaction times in software development to frequent changes in competitive markets.Typically in these scenarios, process models are developed, maintained, and transformed in a team environment by several stakeholders that are often from different business units, resulting in different versions. To obtain integrated process models comprising the changes applied to different versions, the versions need to be consolidated by means of model change management. Change management for process models can be compared to widely used concurrent versioning systems (CVS) and consists of the following major activities: matching of process models, detection of differences, computation of dependencies and conflicts between differences, and merging of process models.Although in general model-driven development (MDD) is accepted as a well-established development approach, there are still some shortcomings that let developers decide against MDD and for more traditional development paradigms. These shortcomings comprise a lack of fully integrated and fully featured development environments for MDD, such as a comprehensive support for model change management.In this thesis, we present a framework for process model change management. The framework is based on an intermediate representation for process models that serves as an abstraction of specific process modeling languages and focuses on common syntactic and semantic core concepts for the modeling of workflow in process models. Based on the intermediate representation, we match process models in versioning scenarios and compute differences between process models generically. Further, we consider the analysis of dependencies between differences and show how conflicts between differences can be computed by taking into account the semantics of the modeling language.As proof-of concept, we have implemented major parts of this framework in terms of a prototype. The detection of differences and dependencies contributed also to the Compare & Merge framework for the IBM WebSphere Business Modeler V 7.0 [1] (WBM), which was released as a product in fall 2009.

How to attract applicants in the atlantic versus the asia-pacific region? A cross-national analysis on China, India, Germany, and Hungary. - Baum, M; Kabst, Rüdiger (Journal of World Business (JWB).)

Bootstrapping Skynet: Calibration and Autonomic Self-Control of Structured Peer-to-Peer Networks - Graffi, Kalman; Klerx, Timo (Proceedings of the International Conference on Peer-to-Peer Computing (P2P'13))
Peer-to-peer systems scale to millions of nodes and provide routing and storage functions with best effort quality. In order to provide a guaranteed quality of the overlay functions, even under strong dynamics in the network with regard to peer capacities, online participation and usage patterns, we propose to calibrate the peer-to-peer overlay and to autonomously learn which qualities can be reached. For that, we simulate the peer-to-peer overlay systematically under a wide range of parameter configurations and use neural networks to learn the effects of the configurations on the quality metrics. Thus, by choosing a specific quality setting by the overlay operator, the network can tune itself to the learned parameter configurations that lead to the desired quality. Evaluation shows that the presented self-calibration succeeds in learning the configuration-quality interdependencies and that peer-to-peer systems can learn and adapt their behavior according to desired quality goals.

Gender Effects on Entrepreneurial Intention: A Meta-Analytical Structural Equation Model. - Haus, I; Steinmetz, Holger; Isidor, R; Kabst, Rüdiger (International Journal of Gender and Entrepreneurship (IJGE))

Analyzing observed composite differences across groups: Is partial measurement invariance enough? - Steinmetz, Holger (European Journal of Research Methods for the Behavioral and Social Sciences.)

Beschleunigung von Tiefenberechung aus Stereobildern durch FPGA-basierte Datenflussrechner - Bick, Christian

Bandbreiten-beschränktes Scheduling mit skalierbaren Jobanforderungen in Multiprozessor-Umgebungen - Meschede, Julian

Automated Service Composition for On-the-Fly SOAs - Huma, Zille; Gerth, Christian; Engels, Gregor; Juwig, Oliver (Proceedings of the 11th International Conference on Service Oriented Computing (ICSOC'13))
In the service-oriented computing domain, the number of available software services steadily increased in recent years, favored by the rise of cloud computing with its attached delivery models like Software-as-a-Service (SaaS). To fully leverage the opportunities provided by these services for developing highly flexible and aligned SOA, integration of new services as well as the substitution of existing services must be simplified. As a consequence, approaches for automated and accurate service discovery and composition are needed. In this paper, we propose an automatic service composition approach as an extension to our earlier work on automatic service discovery. To ensure accurate results, it matches service requests and available offers based on their structural as well as behavioral aspects. Afterwards, possible service compositions are determined by composing service protocols through a composition strategy based on labeled transition systems.

Auktionen im Beschaffungsmanagement - Eine spieltheoretische Analyse - Meckenstock, Kevin

Attributbasierte Verschlüsselung mittels Gittermethoden - Mathematische Grundlagen, Verfahren und Sicherheitsbeweise - Kohn, Kathlén

Asymmetric Nash bargaining solutions and competitive payoffs - Brangewitz, Sonja; Gamp, Jan-Philip (Economics Letters)
We establish a link between cooperative and competitive behavior. For every possible vector of weights of an asymmetric Nash bargaining solution there exists a market that has this asymmetric Nash bargaining solution as its unique competitive payoff vector.

Approximation Algorithms for the Linear Arrangement of Special Classes of Graphs - Setzer, Alexander